SOCIAL FACTORS CAUSING CORRUPTION AND MECHANISMS OF FIGHTING IT (Scientific journal of the Fergana State University, 2023)
This article theoretically explains the social factors that cause corruption and corrupt behavior, their types, and the content of anti-corruption mechanisms.